My first ukrainian people, relationships & adjectives picture book with english translations ebook Teach & learn basic ukrainian words for children, #13. - S, Aneta (Teach & Learn Basic Ukrainian words for Children, 2019)
Did you ever want to teach your kids People, Relationships & Adjectives in Ukrainian ? Learning Ukrainian can be fun with this picture book. In this book you will find the following features: Ukrainian People, Relationships & Adjectives Names Colorful Pictures of People, Relationships & Adjectives English People, Relationships & Adjectives Names